Pan-cancer analysis suggests histocompatibility minor 13 is an unfavorable prognostic biomarker promoting cell proliferation, migration, and invasion in hepatocellular carcinoma - Liu, Jun; Li, Wenli; Wu, Liangyin (Frontiers in Pharmacology, 2022)
Histocompatibility Minor 13 (HM13) encoding the signal peptide peptidase plays an important role in maintaining protein homeostasis but its role in tumors remains unclear. In this study, 33 tumor RNA-seq datasets were extracted from The Cancer Genome Atlas (TCGA) database, and the pan-cancer expression profile of HM13 was evaluated in combination with The Genotype-Tissue Expression (GTEx) datasets. The prognostic significance of abnormal HM13 pan-cancer expression was evaluated by univariate Cox regression and Kaplan-Meier analyses. Co-expression analysis was performed to examine the correlation between abnormal pan-cancer expression of HM13 and immune cell infiltration, immune checkpoint, molecules related to RNA modification, tumor mutational burden (TMB), microsatellite instability (MSI), and other related molecules. CellMiner database was used to evaluate the relationship between the expression of HM13 and drug sensitivity. The results showed overexpression of HM13 in almost all tumors except kidney chromophobe (KICH). Abnormally high expression of HM13 in adrenocortical carcinoma (ACC), kidney renal papillary cell carcinoma (KIRP), uveal melanoma (UVM), liver hepatocellular carcinoma (LIHC), brain lower grade glioma (LGG), head and neck squamous cell carcinoma (HNSC), and kidney renal clear cell carcinoma (KIRC) was associated with poor prognosis. Expression of HM13 correlated strongly with pan-cancer immune checkpoint gene expression and immune cell infiltration. Drug sensitivity analysis indicated that the expression of HM13 was an excellent predictor of drug sensitivity. We verified that both mRNA and protein levels of HM13 were abnormally upregulated in HCC tissues, and were independent risk factors for poor prognosis. Furthermore, interference with HM13 expression in Huh-7 and HCCLM3 cells significantly inhibited proliferation, migration, and invasion. Therefore, our findings demonstrate that HM13 is a potential pan-cancer prognostic marker, thus providing a new dimension for understanding tumor development.